(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to develop interesting, interactive, and appropriate media for students to use in Civic Education (PKn), which is a key component of effective learning materials. This research uses the Research and Development (R&D) method. Interview sheets and questionnaires are data collection techniques used. The products developed are made by utilizing interactive elements such as animations, tests, and short films that are relevant to the content of citizenship and tailored to the needs of elementary school students. The data obtained were analyzed quantitatively and qualitatively. The results in the form of products that are considered worthy of being tested. The results of the trial show that this media can improve the understanding of the subject matter and increase student involvement in the learning process. Analysis of student learning outcome data before and after the use of media showed a significant increase in average scores. PowerPoint-based interactive learning materials can be a useful substitute to improve student achievement in PKn courses. This media can also make learning more fun and meaningful, so it can be used in various classroom settings to encourage creative and active learning